Increased surface area during sintering of calcium phosphate glass and sodium chloride mixtures. Issue 1 (January 2015) - Davim, E.J.C.; Fernandes, M.H.V.; Senos, A.M.R.
Abstract: Glass scaffolds were obtained by the salt sintering method, using mixtures of calcium phosphate glass, 25.42%SiO2 –10.89%P2 O5 –32.68%CaO–31%MgO(mol%), and salt, NaCl, pressed and sintered bellow the salt melting point, followed by leaching of the salt in water. The sintering behaviour of glass/salt powder mixtures was followed by dilatometry, BET and SEM. It was found that the specific surface area (SSA) of supports sintered between 700–750 °C and leached, can be 15–50 times higher than that of the glass precursor powder, a very surprising behaviour because it presents the opposite tendency of a typical sintering process. Dilatometric curves showed an unusual expansion from ∼450 °C until ∼700 °C, followed by shrinkage at higher temperatures. This expansion accompanies the observed increase of SSA and the microstructures showed a clear effect of reaction between the glass and the salt with remarkable wrinkling of the glass particle surfaces. This phenomenon was further investigated by using DTA, XRD and FTIR.